2007
DOI: 10.1002/path.2145
|View full text |Cite
|
Sign up to set email alerts
|

Packaging of prions into exosomes is associated with a novel pathway of PrP processing

Abstract: Prion diseases are fatal, transmissible neurodegenerative disorders associated with conversion of the host-encoded prion protein (PrP(C)) into an abnormal pathogenic isoform (PrP(Sc)). Following exposure to the infectious agent (PrP(Sc)) in acquired disease, infection is propagated in lymphoid tissues prior to neuroinvasion and spread within the central nervous system. The mechanism of prion dissemination is perplexing due to the lack of plausible PrP(Sc)-containing mobile cells that could account for prion sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
341
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(355 citation statements)
references
References 46 publications
12
341
0
2
Order By: Relevance
“…50 Exosomes are small vesicles that can break off from the endocytic machinery of one cell, transverse the extracellular space, and then fuse with the outer membrane of another cell, thus transferring their contents to the new cell. 51 Of relevance to other neurodegenerative disorders, they have been shown to transmit pathogenic prion proteins [52][53][54] and b-amyloid (Ab) aggregates. 55 Recently, a-syn-containing exosomes secreted from neuroblastoma cells overexpressing a-syn were found to transfer a-syn to other cultured neuroblastoma cells.…”
Section: Molecular Mechanisms Involved In Intercellular Transfer Of Amentioning
confidence: 99%
“…50 Exosomes are small vesicles that can break off from the endocytic machinery of one cell, transverse the extracellular space, and then fuse with the outer membrane of another cell, thus transferring their contents to the new cell. 51 Of relevance to other neurodegenerative disorders, they have been shown to transmit pathogenic prion proteins [52][53][54] and b-amyloid (Ab) aggregates. 55 Recently, a-syn-containing exosomes secreted from neuroblastoma cells overexpressing a-syn were found to transfer a-syn to other cultured neuroblastoma cells.…”
Section: Molecular Mechanisms Involved In Intercellular Transfer Of Amentioning
confidence: 99%
“…This "Trojan exosome" hypothesis, posited by Gould et al (39), is currently being evaluated in protein-misfolding neurodegenerative diseases as a possible mechanism for the spread of misfolded proteins (40 -45). Cellular prion protein (PrP C ) and misfolded PrP TSE have been identified in exosomes from various TSE models (46 -55) and intracerebral inoculation of exosomes obtained from TSE-infected cell cultures has caused clinical disease in mice (47,49). Little is known about the distribution of PrP TSE in blood.…”
mentioning
confidence: 99%
“…Février et al first reported that abnormal PrP and infectivity actively released from sheep scrapie-infected MovS and Rov cells was associated with small vesicles (50-100 nm) called exosomes [46], raising the possibility that infected exosomes could serve as a vehicle for prion dissemination [108]. Similar findings were later obtained for GT1 cells infected with a mouse-adapted prion strain, indicating that potential spread of infection through cell-free mechanisms is probably not restricted to a particular type of cell or strain [143]. A further support for cell-free transmission of prions was gained by Leblanc et al who showed that retrovirus infection enhances prion infectivity release [76].…”
Section: De Novo Infection and Cell-to-cell Dissemination Of Prionsmentioning
confidence: 52%
“…It was recently demonstrated that exosomes released by MovS and Rov cells do contain abnormal PrP and prion infectivity when the cells were infected with a sheep scrapie agent [46]. A similar observation was subsequently reported for GT1 cells infected with a mouse-adapted prion strain [143]. Exosomes are formed in multivesicular bodies (MVB), which could therefore represent an intracellular site for PrP Sc accumulation.…”
Section: Cell Models Propagating Naturally-occurring Prion Isolatesmentioning
confidence: 54%